Melatonin vs. dexmedetomidine for sleep induction in children before electroencephalography - Katja Peganc Nunčič; David Neubauer; David Neubauer; Jasna Oražem Mrak; Mirjana Perković Benedik; Mirjana Perković Benedik; Urška Mahne; Neli Bizjak; Zvonka Rener Primec; Zvonka Rener Primec; Nataša Šuštar; Tita Butenko; et al. (Frontiers in Pediatrics, 2024)
Background and objectivesIn children requiring electroencephalography (EEG), sleep recording can provide crucial information. As EEG recordings during spontaneous sleep are not always possible, pharmacological sleep-inducing agents are sometimes required. The aim of the study was to evaluate safety and efficacy of melatonin (Mel) and dexmedetomidine (Dex; intranasal and sublingual application) for sleep induction prior to EEG.MethodsIn this prospective randomized study, 156 consecutive patients aged 1–19 years were enrolled and randomized by draw into melatonin group (Mel; n = 54; dose: 0.1 mg/kg), dexmedetomidine (Dex) sublingual group (DexL; n = 51; dose: 3 mcg/kg) or dexmedetomidine intranasal group (DexN; n = 51; dose: 3 mcg/kg). We compared the groups in several parameters regarding efficacy and safety and also carried out a separate analysis for a subgroup of patients with complex behavioral problems.ResultsSleep was achieved in 93.6% of participants after the first application of the drug and in 99.4% after the application of another if needed. Mel was effective as the first drug in 83.3% and Dex in 99.0% (p < 0.001); in the subgroup of patients with complex developmental problems Mel was effective in 73.4% and Dex in 100% (p < 0.001). The patients fell asleep faster after intranasal application of Dex than after sublingual application (p = 0.006). None of the patients had respiratory depression, bradycardia, desaturation, or hypotension.ConclusionsMel and Dex are both safe for sleep induction prior to EEG recording in children. Dex is more effective compared to Mel in inducing sleep, also in the subgroup of children with complex behavioral problems. Clinical Trial RegistrationDexmedetomidine and Melatonin for Sleep Induction for EEG in Children, NCT04665453.